2020
DOI: 10.3390/ma13214980
|View full text |Cite
|
Sign up to set email alerts
|

Triboelectric Energy Harvesting Response of Different Polymer-Based Materials

Abstract: Energy harvesting systems for low-power devices are increasingly being a requirement within the context of the Internet of Things and, in particular, for self-powered sensors in remote or inaccessible locations. Triboelectric nanogenerators are a suitable approach for harvesting environmental mechanical energy otherwise wasted in nature. This work reports on the evaluation of the output power of different polymer and polymer composites, by using the triboelectric contact-separation systems (10 N of force follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Over the years, significant progress has been made in developing numerous new classes of polymeric and composite polymeric materials for T.E.N.G.s. It has been observed that composite polymeric materials have yielded better output performance compared to using only polymeric materials in most cases [27,32]. Thus, it can be said that polymer-based composites hold immense potential for energy harvesting applications owing to their flexible nature, suitable voltage providing sufficient power output, lower manufacturing costs, and quick processing.…”
Section: Types Of Composite Materials Used In Energy Harvestingmentioning
confidence: 99%
“…Over the years, significant progress has been made in developing numerous new classes of polymeric and composite polymeric materials for T.E.N.G.s. It has been observed that composite polymeric materials have yielded better output performance compared to using only polymeric materials in most cases [27,32]. Thus, it can be said that polymer-based composites hold immense potential for energy harvesting applications owing to their flexible nature, suitable voltage providing sufficient power output, lower manufacturing costs, and quick processing.…”
Section: Types Of Composite Materials Used In Energy Harvestingmentioning
confidence: 99%
“…The discovery of new, advanced materials in renewable energy (biogas, solar energy, energy harvesting, etc.) and energy storage systems [89][90][91][92][93][94][95][96][97][98] is an actual research challenge. The AI algorithms driving circuits are surely tools supporting the increase of the energy conversion efficiency-for example, by…”
Section: (Ket Ii) Advanced Materialsmentioning
confidence: 99%
“…Polymer fibers can be made by several techniques like electrospinning, phase separation, melt-blown, and wet spinning . Few research groups have already reported various polymeric-based TENGs such as polyamide, polyethylene, polyvinylidene fluoride, Teflon, polyvinyl chloride, polyimide, polyester, and polyurethane that have been reported for energy harvesting applications. ,, Out of them, polyurethane has an elastic property, and it can be a better choice for flexible electronics. However, limited studies have been reported on polyurethane-based TENGs, and few are shown in the Supporting Information, Table S1.…”
Section: Introductionmentioning
confidence: 99%